The effect of ephedrine on intraoperative hypothermia - Youn Yi Jo (Korean Journal of Anesthesiology, 2011)
BackgroundPrevention of intraoperative hypothermia has become a standard of operative care. Since ephedrine has a thermogenic effect and it is frequently used to treat hypotension during anesthesia, this study was designed to determine the effect of ephedrine on intraoperative hypothermia of patients who are undergoing spine surgery.MethodsTwenty-four patients were randomly divided to receive an ephedrine (the ephedrine group, n = 12) or normal saline (the control group, n = 12) infusion for 2 h. The esophageal temperature (the core temperature), the index finger temperature (the peripheral temperature) and the hemodynamic variables such as the mean blood pressure and heart rate were measured every 15 minutes after the intubation.ResultsAt the end of the study period, the esophageal temperature and hemodynamic variables were significantly decreased in the control group, whereas those in the ephedrine group were stably maintained. The index finger temperature was significantly lower in the ephedrine group compared to that in the control group, suggesting the prevention of core-to-peripheral redistribution of the heat as the cause of temperature maintenance.ConclusionsAn intraoperative infusion of ephedrine minimized the decrease of the core temperature and it stably maintained the hemodynamic variables during spine surgery with the patient under general anesthesia.